2013
DOI: 10.4103/1735-3327.113325
|View full text |Cite
|
Sign up to set email alerts
|

Demographic distribution of odontogenic cysts in Isfahan (Iran) over a 23-year period (1988-2010)

Abstract: Background:Odontogenic cysts are relatively common lesions which can cause different complications. As demographic information is lacking in Iran and specially in Isfahan, the aim of this study was to determine the prevalence of odontogenic cysts according to age, gender and affected area among patients referring to the Oral Pathology Department of the Dental School of Isfahan University of Medical Sciences (Iran) over a 23-year period.Materials and Methods:A total of 7412 diagnosed lesions recorded in the Ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
15
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 20 publications
8
15
0
2
Order By: Relevance
“…In this retrospective study based on pathology material, the demographic and clinical features of 5294 jaw cysts are described. In Table 5, the results of the present study are compared to those of previous ones with a sample of at least 1000 patients [2,[10][11][12][13][14][15][16][17]. It should be noted that the sample size of the present study is the 3rd largest in the literature following Daley's et al [17] and Jones' and Franklin's [2] investigations.…”
Section: Discussionmentioning
confidence: 84%
“…In this retrospective study based on pathology material, the demographic and clinical features of 5294 jaw cysts are described. In Table 5, the results of the present study are compared to those of previous ones with a sample of at least 1000 patients [2,[10][11][12][13][14][15][16][17]. It should be noted that the sample size of the present study is the 3rd largest in the literature following Daley's et al [17] and Jones' and Franklin's [2] investigations.…”
Section: Discussionmentioning
confidence: 84%
“…It means that despite the number of referred patients to this center, cases with smaller cysts which can be treated under local anesthesia would not be admitted to this hospital. In similar studies performed on the Iranian population ( 16 - 18 ) the radicular cyst was the most common odontogenic cyst whilst the dentigerous cyst was the most frequent developmental one. Based on these results, it is concluded that OKC is in the third level and is very frequent among Iranians.…”
Section: Discussionmentioning
confidence: 85%
“…Some investigations reported the prevalence of such cysts in Iranian population, although they were local studies and there is no consensus on the definite effects and associated factors in the developing odontogenic cysts ( 16 - 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of all odontogenic cysts, OKC represents about 6 to 25.7% and appears to be more frequent in males with a peak incidence of 20-30 years of age. This lesion deserves differential considerations due to its clinical presentation, since it presents invasive-infiltrative growth, expanding in great proportions, causing considerable bone destruction usually before any symptoms (5,8,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%